Religious tolerance conceptual framework: Malaysian religious leaders and scholars’ perspective - Nur Farhana Abdul Rahman; Nur Solehah Shapiee (Penerbit Universiti Kebangsaan Malaysia, 2023)
Religious tolerance is an important element in developing the balance and harmony of Malaysia's pluralistic society. Despite this, there are still some irresponsible parties that continuously advocate sensitive issues, especially religious rights, that cause intolerance in society. This situation has contributed to the generation of negative impacts on inter religious relationships among the communities in Malaysia. Thus, this paper aims to discuss the religious tolerance framework for Muslim and non-Muslim relations in Malaysia. This study uses qualitative methods and a phenomenological research design. The goal of the phenomenological approach is to understand the subject of the study through their views and perspectives. The information from this interview is the main data for this research. A total of 13 representatives and experts from each major religion in Malaysia, namely Islamic, Christian, Hindu, and Buddhist (represented by mufti academics, scholars, and religious leaders), were involved as informants for this study. The interview method conducted with 13 religious representatives in Malaysia will be analysed to get their perceptions on the formation of religious tolerance guidelines in Malaysia. This study found that in the context of the conceptual understanding of religious tolerance, Muslim and non-Muslim communities emphasise three main values: respect, forgiveness, and doing good deeds. They understand that religious tolerance means adhering to one’s own religion, respecting the religious beliefs of others, and being willing to forgive and do good deeds for those of different religions. This form of understanding of the meaning of tolerance refutes the concept of religious pluralism, which promotes the idea of unity among all religions as a way to establish religious tolerance in a society.